2003
DOI: 10.2118/84940-pa
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Effects in Gas-Condensate Recovery and Gas-Injection Processes

Abstract: Summary This paper evaluates the behavior of the dimensionless numbers that gauge the gas/oil interfacial tension (IFT) with respect to the other forces (viscous and buoyancy forces) involved in two-phase flow through porous media. These numbers, referred to respectively as the capillary and Bond numbers, diverge on approach to gas/oil complete miscibility, meaning that viscous and buoyancy forces become dominant over capillary forces. The divergence behaves as a power of the distance to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It should be noted that capillary end effects (which appear in water-wet plugs and which retain water at the outlet of the plug) may be significant in our study because of the small plug size; in field operations this effect can be neglected, and the residual saturations measured in our study may therefore not be representative of the true field-scale residual saturations. In addition we would like to stress that for CO 2 -oilwater systems, a spreading coefficient close to zero (spreading situation) is expected [60], and this may change the fluid dynamics and/or thermodynamic fluid-fluid-fluidsolid pore-scale arrangement significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that capillary end effects (which appear in water-wet plugs and which retain water at the outlet of the plug) may be significant in our study because of the small plug size; in field operations this effect can be neglected, and the residual saturations measured in our study may therefore not be representative of the true field-scale residual saturations. In addition we would like to stress that for CO 2 -oilwater systems, a spreading coefficient close to zero (spreading situation) is expected [60], and this may change the fluid dynamics and/or thermodynamic fluid-fluid-fluidsolid pore-scale arrangement significantly.…”
Section: Discussionmentioning
confidence: 99%
“…30 For instance, efficient semi-miscible displacement (emulsion-like) with low residual oil saturation occurs in a very low IFT system; while at high IFT the displacement changes to a low efficiency capillary dominated flow. 31 The behavior of IFT at different pressures was first studied during the 1980s. 32 These studies proved that the existence of asphaltene in oil considerably affects the interfacial behavior resulting in higher gas−oil IFT especially at high pressures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A number of technical papers have been published to address the role of rock wettability in oil recovery, most of which suggest that compositional changes in either the oil phase or the aqueous phase can alter wettability of rock surfaces. ,, The salinity of the connate water has been found to be a primary factor controlling the oil recovery because increased salinity can cause wettability alternation from the water-wet condition to the mixed-wet condition . In gas miscible processes, it is found from experiments that the ultimate oil recovery is the highest for the oil−wet rock−fluids system and lowest for the water−wet rock−fluids system, respectively. , In a CO 2 flooding process, the reservoir rock becomes less oil-wet after CO 2 injection. , It has also been found that the wettability alteration occurs for a CO 2 −water−coal system, a CO 2 −water−glass system and a CO 2 −synthetic brine−mica/quartz system, and a CO 2 −reservoir brine−reservoir rock system, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A number of technical papers have been published to address the role of rock wettability in oil recovery, most of which suggest that compositional changes in either the oil phase or the aqueous phase can alter wettability of rock surfaces. 15,16,[19][20][21] The salinity of the connate water has been found to be a primary factor controlling the oil recovery because increased salinity can cause wettability alternation from the water-wet condition to the mixed-wet condition. 22 In gas miscible processes, it is found from experiments that the ultimate oil recovery is the highest for the oil-wet rock-fluids system and lowest for the water-wet rock-fluids system, respectively.…”
Section: Introductionmentioning
confidence: 99%